THE NEGATIVE EXPERIENCES OF SEAFARERS: THEIR PECULIARITIES AND CORRECTIVE PSYCHOPROPHYLAXIS - Lileikis, Saulius (Acta Paedagogica Vilnensia, 2008)
Directions of optimisation of seafarers’ psycho-hygiene and prophylactic position of maritime students are developed in this article. Psychological panorama of seafarers’ emotional conditions is revealed. Optimal possibilities of conducting psycho-pro- phylactics for seafarers in the conditions of extreme work are indicated. The spectrum of seafarers’ main emotional conditions is composed of isolation and monotony, the experience of loneliness and stress. Seafarers’ experience hunger for new effects, general laxity, worry, reticence and depression. The afferentation and watchfulness are abating. Some phases of hypnosis start to develop. For seafarers it is hard to keep the positive psychological climate in the group isolation. The system of psychoprophylactic means is created for optimisation of seafarers’ psychohygiene. The place of work and rest, the layout of rooms, the position of things and color stimulate good temper. In the conditions of extreme work seafarers’ psychic health is positively stimulated by possibility to stay close to natural compositions of growing plants. Those are made in closed technical systems. Living nature images on TV or Internet is a partial addition to that. It is very important to listen to favorite music to overcome monotony of emotions. The research shows that functional music is effective for abating trouble and drowsiness while working in extreme conditions. It is important to find time for an interesting and enriching book in conditions of isolation and loneliness. If it is possible, it is necessary to watch similar TV editions or browse similar Internet sites. General principle of optimisation of seafarers’ psychohygiene is composed of approximation of their extreme work to normal living conditions. The tendencies of maritime students prophylactic position are similar in both age groups. First- year maritime students give some theoretic-idealistic direction of their prophylactic position. Third year maritime students present the beginning of middle youth. Their prophylactic position is more mature, weighed and practical. The effective education of sport, art, authority, nature, esthetics, work must correct the prophylactic position of maritime students. This is the direction of their psycho prophylactic orientation. It is especially significant for the future seafarers’ psychohygiene in their extreme work.